Defining Stage Argumentation Semantics in Terms of an Abducible Semantics - Osorio, Mauricio; Carballido, José Luis; Zepeda, Claudia (Electronic notes in theoretical computer science, 2016)
We define a new logic programming semantics in terms of abducible atoms. We use it to characterize the stage extensions of an argumentation framework AF by means of an associated normal program PAF. We also define the stage semantics for a special type of normal programs and present a similar characterization.